2016
DOI: 10.24953/turkjped.2016.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vascular anomalies: a review of clinical and radiological findings of cases presenting with different complaints in childhood

Abstract: Congenital pulmonary vascular abnormalities arise from several etiologies. These anomalies are difficult to categorize and sorted into distinct classifications. Major pulmonary vascular abnormalities can be ranked as interruption of the main pulmonary artery or its absence, emergence of the left pulmonary artery in the right pulmonary artery, pulmonary venous drainage abnormalities, and pulmonary arteriovenous malformations (PAVMs). Some of the cases are asymptomatic and diagnosed by coincidence, whereas a few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In conditions with pulmonary hypoplasia, operative intervention ought only to be sought in cases in which cardiac and vascular abnormalities are present, persistent episodes of hemoptysis, or chronic chest infections and bronchiectasis [ 6 ]. Major pulmonary vascular abnormalities include interruption of the main pulmonary artery or its absence, the emergence of the left pulmonary artery in the right pulmonary artery, pulmonary venous drainage abnormalities, and pulmonary arteriovenous malformations (PAVMs) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conditions with pulmonary hypoplasia, operative intervention ought only to be sought in cases in which cardiac and vascular abnormalities are present, persistent episodes of hemoptysis, or chronic chest infections and bronchiectasis [ 6 ]. Major pulmonary vascular abnormalities include interruption of the main pulmonary artery or its absence, the emergence of the left pulmonary artery in the right pulmonary artery, pulmonary venous drainage abnormalities, and pulmonary arteriovenous malformations (PAVMs) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical intervention depends on many aspects as overall clinical status, radiological investigation, and the severity of vascular and cardiac abnormalities and associated symptoms. We have looked into this further, however, the decision of continuing the conservative management only or surgical intervention is determined after considering all aspects [ 10 , 11 , 12 ]. A multidisciplinary team is now following up with the patient which consists of a thoracic surgeon, a pediatrician, and a radiologist.…”
Section: Discussionmentioning
confidence: 99%
“…Because PAVM does not affect cardiac hemodynamics, most patients remain asymptomatic and are easily misdiagnosed. Unless the shunt flow of PAVM is > 20.0% of the total systemic circulation, it may show asymptomatic hypoxemia, dyspnea, hemoptysis, chest pain, shortness of breath after activity, clubbing fingers, cyanosis, dizziness, ischemic stroke, TIA, and so on [ 16 18 ]. However, CS as a result of PE caused by PAVM is relatively rare in the clinic, as previous studies reported [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%